Long-term variability of zooplankton community under climate warming in tropical eutrophic man-made lake - SUNARDI SUNARDI; TAKAO YOSHIMATSU; NIKO JUNIANTO; NADIA ISTIQAMAH; TYRELL DEWEBER (Biodiversitas Journal of Biological Diversity, 2016)
Sunardi, Yoshimatsu T, Junianto N, Istiqamah N, DeWeber T. 2016. Long-term variability of zooplankton community under climate warming in tropical eutrophic man-made lake. Biodiversitas 17: 634-641. The climate warming is increasingly acknowledged as an important driver of lake ecosystems. However, there are no generic patterns of how the aquatic species/community responds the warming climate; instead the changes are complicated by interactions of many factors. To regard the important role of zooplankton in the lake ecosystems, this paper questions whether the climate warming affects their community structure in tropical eutrophic man-made lake. We analyzed a series of data resulted from a long water quality monitoring activities in the Cirata Lake, Indonesia. We anticipated that there would be a strong association between the climates warming with the response of zooplankton community after 19 years. Our result suggested that the lake has been becoming slightly warmer following the atmospheric temperature. Instead of decreasing, the shifting water temperature tend promotes a greater species richness, density, and diversity of the zooplankton. Relevant changes inspecies composition have been observed. It seems that the magnitude of the shift of the temperature, and the eutrophication status played an important role in shaping the changes of the zooplankton community structure.